MiR‐1, regulated by LMP1, suppresses tumour growth and metastasis by targeting K‐ras in nasopharyngeal carcinoma. Issue 6 (19th January 2016) - Chen, Xi; Shi, Jingxuan; Zhong, Jianwen; Huang, Zhenyun; Luo, Xi; Huang, Yaping; Feng, Shuang; Shao, Jianbo; Liu, Dabo
Summary: There is evidence to show that downregulation of miR‐1 expression is closely related to cancer progression, including in nasopharyngeal carcinoma (NPC). However, the molecular mechanisms underlying miR‐1 downregulation in NPC remain largely unknown, especially its association with Epstein–Barr virus (EBV). In this study we found that restoration of miR‐1 dramatically inhibited cell invasion in vitro, together with tumour growth and metastasis in vivo . Importantly, we found that LMP1, an Epstein–Barr virus (EBV)‐associated protein, suppressed miR‐1 expression. Furthermore, we identified K‐ras as a novel direct target of miR‐1. Our results demonstrated for the first time that miR‐1 was suppressed by LMP1 and its tumour‐suppressive effects were mediated chiefly by repressing K‐ras expression. We propose that miR‐1 could serve as an independent biomarker to identify patients with different clinical characteristics.